Parenting in Multicultural Settings: Experiences of the Indonesian Mothers - Pertiwi, Yopina G.; Babu, Nandita (ANIMA Indonesian Psychological Journal, 2010)
This study was an attempt to explore the experiences of Indonesian women who married to foreign spouses in the course of parenting. Six Indonesian women were interviewed following a semi- structured interview schedule. While all the participants were Indonesian in origin, their spouses were from different countries, that is India, Japan, Netherland, USA, Scotland, and Germany. The participants and their spouses differ in their parenting strategies, which can be attributed to the cultural differences between them. However, it was also observed that the spouses manage these differences by applying several strategies, such as learning from each other, tolerating each other’s standards, and mixing up the cultural values. The acculturation effect of the partner’s culture is being discussed in this study. Penelitian ini bertujuan mengetahui pola pengasuhan anak yang dilakukan perempuan Indonesia yang menikah dengan pria asing. Enam perempuan Indonesia berpartisipasi dalam penelitian yang menggunakan metode wawancara semi-terstruktur. Keenam partisipan berasal dari Indonesia, sedangkan suami mereka berasal dari berbagai negara, yaitu India, Jepang, Belanda, Amerika Serikat, Skotlandia, dan Jerman. Partisipan dan pasangannya memiliki perbedaan dalam strategi pengasuhan anak yang disebabkan perbedaan budaya di antara mereka. Namun, hasil penelitian juga menunjukkan bahwa pasangan tersebut dapat mengatasi perbedaan yang muncul dengan mengaplikasikan beberapa strategi, seperti saling belajar satu sama lain, menoleransi standar masing- masing, dan melakukan pencampuran nilai-nilai budaya. Pengaruh akulturasi dari budaya asal pasangan juga didiskusikan dalam artikel ini.